Project Report Serial Interfacing Between External Sensors and NCS Console of Data Link - SHASHWATI SHEEL and VIDHYASHREE C (2011)
INTERNAL GUIDE : Sathiya P EXTERNAL GUIDE : Kavitha S K USN NO : 1MJ08EC082 and 1MJ08EC101 CARRIED OUT AT : BEL Bangalore- ACC NO : PR1845
Keywords: Console of Data Link